(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2018)
Research background. Epilepsy is not only a central nervous system or brain disorder. It is a biological, psychological and social condition (Scambler, 2010). Children with epilepsy have a higher risk of having psychological disorders such as depression, anxiety and attention defcit disorders. The application of art therapy for people with epilepsy helps to express and understand feelings more eﬀectively (Shore, 2014). Unfortunately, there is a lack of research that analyses the experience of epilepsy patients in art therapy. The aim of this article is to reveal and describe experiences of epileptic people during art therapy. Research questions: What experiences of epilepsy patients predominate in the collected thematic analysis data? What formal elements of drawing reﬂect the participants’ experiences? How does thematic analysis data relate to the data of formal elements analysis of drawings? Methods. Qualitative study in which the participants of the study were subjected to group art therapy. The data was analysed by the thematic method and the analysis of formal elements of the drawings. Results. The analysis of the verbal data revealed the individual themes of the study participants’ experiences. After drawing analysis formal elements were found that expressed the participants’ experiences. Conclusions. 1. Experiences dominating in thematic analysis are loneliness and confnement during difcult moments, as well as constant tension and internal confusion. 2. The experiences of research participants are reﬂected in these repeated formal elements of drawing: the use of confnes and framing, the use of black and red collars, fgurative and abstract depictions, the chaotic nature of the composition, the lack of concreteness in shapes, expressiveness, and incompleteness. 3. The thematic and formal drawing element analyses complement each other. Drawings that convey the illness-related experiences include confnes, framing, and black colour in the main elements of the composition. Drawing that reﬂects unpleasant feelings and experiences uses abstract depiction, chaotic compositions, the lack of concreteness in shapes, expressiveness and incompleteness. Keywords: epilepsy, art therapy, psychosocial risks.